PENGEMBANGAN BAHAN AJAR CD INTERAKTIF MATERI SUHU DAN KALOR BERBENTUK POWERPOINT MATERI SUHU DAN KALOR UNTUK PEMBELAJARAN FISIKA KELAS X SMA - Annisa Septiani (PILLAR OF PHYSICS EDUCATION, 2013)
Interactive Compact Disk (CD)  is one of teaching media that can be used by physics teacher to teach abstract concept like heat and temperature. There are some of the Heat and Temperature concept is abstract, such as the flow of heat on conduction and convecton process that difficult by the student to learn it optimally if only use the printing media. We can make the animation of the abstract concept by using CD interactive, to make the comprehension of the student to Heat and Temperature concept can be optimally. The aim of this research are to product teaching media as interactive CD which has high validity, practicality, and effectivity. This interactive CD will used by senior high school student grade X in physics learning. The type of the Research and Development (R & D). Instrument of research are used form of validity, student and teacher’s response for practicality, effectivity form, and pretest and postest result. Interactive CD are made using Powerpoint software for heat and temperature material. The value of validity is 89, 53 that mean this interactive CD is very valid. Teacher’s respons value is 100 that show this interactive CD is very practice. Student’s respons value is 89 2 that show this interactive CD is very practice in use by students. This interactive CD is very effective that show by effectivity value (89,42) and increasing of postes value 45,28 to be 70,88.   Keywords: Interactive CD, Powerpoint, Heat and Temperature